2017
DOI: 10.21608/adjg.2017.5191
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Types of Luting Cements on Retention and Marginal Adaptation of Implant-Supported Crowns (An in Vitro Study)

Abstract: Aim:The purpose of this study was to evaluate the retention values and marginal adaptation of implant-supported metal copings using different luting agents. Material and Method:Forty implant fixtures and solid abutments of 7mm height were embedded vertically in epoxy resin blocks. Metal copings with a loop on the occlusal surface were fabricated using base metal alloy. The copings were luted using four different cements (Multilink N, Fuji Plus, Fuji1 and Adhesor) under static load of 5kg (n=10). All specimens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Ahmed et al assessed the retention values and marginal adaptation of implant-supported metal copings using different luting agents. They concluded that resin cement, resin-modified glass ionomer, and zinc phosphate had statistically the same retentive quality [ 17 ]. Resin cement has a retention strength almost twice that of resin-modified glass ionomer [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ahmed et al assessed the retention values and marginal adaptation of implant-supported metal copings using different luting agents. They concluded that resin cement, resin-modified glass ionomer, and zinc phosphate had statistically the same retentive quality [ 17 ]. Resin cement has a retention strength almost twice that of resin-modified glass ionomer [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Today, implant use is increasing due to the factors such as 1)Increasing the life expectancy of individuals in society, 2) age-related tooth loss, 3)Consequences of failure of fixed prostheses, 4) anatomic consequences of tooth loss, 5) poor performance of removable dentures, 6) the psychological consequences of tooth loss, 7) the predictable long-term outcomes of implant-based dentures, 8) the benefits of implant-based dentures, and 9) increased public knowledge (3). However, most people have little information about dental implants and their information is sometimes incorrect.…”
Section: Introductionmentioning
confidence: 99%